GREAT-ITN and Gaia: Preparing for Science. Issue 67 (17th July 2015) - Walton, N.A.; Bailer-Jones, C.A.L.; Brown, A.G.A.; Clementini, G.; Eyer, L.; Feltzing, S.; Figueras, F.; Grebel, E.K.; Michalowski, T.; Ridder, J. De; Santos, N.; Smith, M.C.; et al.
Abstract : This paper gives a brief overview of the Gaia Research for European Astronomy Training (GREAT) network, including a description of the GREAT-ESF Research Network Programme and the GREAT Initial Training Network (GREAT-ITN). Scientific highlights from the GREAT-ITN are noted.